NEUROPSYCHIC FEATURES OF FITNESS PRACTICE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
By doing general fitness, you can not only maintain or improve your health, but also regulate your mental (spiritual) state, while the dynamics of the neuropsychic characteristics of people involved in fitness are poorly understood, which determines the relevance of its research. We formulated the purpose of the study: to study the relationship between the physical and mental functions of the human body. In accordance with the purpose of the study, the following tasks were set: to conduct a theoretical analysis of psychological literature on the problem of the influence of physical education and sports on people’s health, their neuropsychic state; consider the concept of “body image” in psychology; reveal the connection between the symbolism of physicality and the localization of the psyche; develop a research program to study the relationship between the physical and mental functions of the human body.